Corrosion resistance of composite oxide film prepared on Ca-added flame-resistant magnesium alloy AZCa612 by micro-arc oxidation. (15th August 2017) - Li, Oi Lun; Tsunakawa, Mika; Shimada, Yuta; Nakamura, Kae; Nishinaka, Kazuhito; Ishizaki, Takahiro
Highlights: A composite layer of MgO and Mg-Mn-Al-Oxide was prepared on flame-resistant AZCa612 by micro-arc oxidation. The corrosion rate of the film coated AZCa612 decreased by 6 orders of magnitude compared to bare substrate. The composite oxide film prepared by MAO showed superior corrosion resistance in 5 wt.% NaCl aqueous solution. Abstract: A composite oxide film was prepared on a flame-resistant magnesium alloy AZCa612 by micro-arc oxidation (MAO). The thickness of the film was approximately 30 μm, where the film was composed of mainly of MgO and Mg-Mn-Al oxide. Potentiodynamic polarization curve measurements demonstrated that the corrosion current density of the composite oxide film coated AZCa612 decreased by 6 orders of magnitude compared to bare substrate. Immersion tests in 5 wt.% NaCl solution after 42 day indicated the coating phase did not change significantly, which proved that the MAO coating have superior corrosion resistance in 5 wt.% NaCl aqueous solution.